From highway to rail? Germany's public transport ticket experiment - Theresa Daniel; Maximilian M. Gail; Phil-Adrian Klotz (Philipps-University Marburg, School of Business and Economics, 2025)
This paper examines the impact of Germany's nationwide 9-Euro-Ticket, a temporary almost fare-free transport ticket, on highway passenger traffic. Using a difference-in-differences approach, we find a significant reduction of approximately 4.5%, primarily driven by decreased weekend traffic. Event study results also indicate considerable heterogeneity across time, federal states, and road types. A similar but more persistent effect is observed for the Deutschlandticket, the permanent successor to the 9-Euro-Ticket. However, our findings suggest that neither ticket has resulted in a lasting shift from private cars to public transport, especially among commuters. Hence, the overall efficiency of this measure remains uncertain, particularly in view of the high direct costs and the necessary investments required to improve Germany's rail infrastructure in the near future.
Keywords: R48; R41; L91; 330; Modal Shift; 9-Euro-Ticket; Deutschlandticket; Difference-in-Differences